Juridical Review of Settlement Regulations : Naughty Debtors In Banking Law In Indonesia - Setyowati, Endang; Ana Kadarningsih (International Journal of Law, Crime and Justice, 2024)
This research was motivated by several cases resulting from the actions of naughty debtors which caused significant losses for Indonesia. There is a legal vacuum in Law Number 10 of 1998 concerning Banking, making it difficult for law enforcers to determine criminal acts committed by naughty debtors. The problem formulation taken is how banking law in Indonesia is in the perspective of legal objective theory, and what is the juridical review of bad debtors in the banking law. This research uses a normative legal research approach with a theory and legal principles approach. Several things need to be reviewed due to the impact caused by Law Number 10 of 1998 concerning Banking, namely that there is an article that can only ensnare bank employees if there is some form of criminal liability. Apart from that, there is no clause that regulates criminal sanctions for bank employees who collude with debtors. Bank Indonesia can impose administrative sanctions, but this authority is not regulated expressly and unequivocally in the Banking Law. So that Bank Indonesia has the potential to abuse its authority in determining actions.